DESIGNED TO BE OVERSPEND: A BEHAVIORAL LOOK INTO MARKETING'S FINANCIAL IMPACT IN THE DIGITAL AGE - Natania Ken Anniko Giamanto; I Gusti Bagus Yosia Wiryakusuma (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
In the digital era, consumer behavior has shifted with the development of technology and marketing strategies. Currently, people are increasingly using e-commerce for buying and selling transactions. They obtain product information that they want to buy from their social media platform. This phenomenon leads to overspending behavior. Overspending can be caused by several factors, including cognitive bias, present bias, and urgency to buy. Therefore, the purpose of this study is to examine the role of cognitive bias, present bias, and urgency to buy in shaping overspending behavior. This research is necessary because the topics related to overspending, cognitive bias, present bias, and urgency to buy are still rarely studied. It is hoped that the results of this study can help develop digital marketing strategies. Respondents in this study were Indonesians of productive age (18-55 years) who actively use social media. Respondents were asked to complete a questionnaire, and all data obtained were processed using the SEM-PLS (Structural Equation Modeling – Partial Least Squares) method. This study shows that cognitive bias mainly influences overspending, cognitive bias influences present bias, present bias influences overspending, and present bias does not mediate the relationship between cognitive bias and overspending. Furthermore, the urgency to buy moderates the existing relationship between present bias and overspending.